INDUSTRIAL LIGHTING AND ITS IMPACT ON OCCUPATIONAL HEALTH AND SAFETY AND ENVIRONMENT - Хмельницкий, Юрий; Мусаткина, Бэла; Игнатов, Олег (Modern engineering and innovative technologies, 2017)
The paper discusses the requirements of Russian and European regulatory documents for lighting work areas. A comparative analysis of the characteristics of modern light sources is given. The results of instrumental measurements of indicators of industrial